UJI EFEK GASTROPROTEKTIF EKSTRAK ETANOL DAUN BIDARA PADA TIKUS ULKUS PEPTIKUM DENGAN PARAMETER pH - safriani- rahman1; Sitti Amirah; Fitriana; Muh. Rayhan Fachreza (Kieraha Medical Journal, 2026)
Peptic ulcer suffered by many people and potentially to cause DRP (Drug Related Problems) and has many severe side effects. Bidara leaves (Ziziphus mauritana Lam.) contain saponins, flavonoids, alkaloids, and tannins that can potentially be an alternative treatment for peptic ulcers. This study aims to see the gastroprotective effect of bidara leaves extract on peptic ulcers in rats based on pH parameters. A total of 15 rats were divided into 5 groups consisting of 1 Normal group, 1 comparison group (Omeprazole 20 mg/kgBW) and 3 treatment groups of bidara leaves extract with doses of 50 mg/KgBW, 150 mg/KgBW, and 250 mg/kgBW. . Administration was carried out orally once a day for 14 days. On the 15th day all test animals were induced with 96% ethanol at a dose of 5 mL/kgBW. Next, all test animals were sacrificed and dissected to remove their stomach organs. The gastroprotective effect was then observed using gastric pH measurements. The results showed that administration of ethanol extract of bidara leaves at a dose of 250 mg/kgBW provided a better gastroprotective effect than other dosage variations and comparisons, as seen from the average gastric pH value of 5.96 ± 1.48.